Development of space truss systems in timber - Mupona, Gaylord Tonderai (Department of Civil Engineering, 2014)
Space trusses are a valuable structural form for architects and structural engineers due mainly to their efficiency in providing large unobstructed areas, associated with faster erection speeds and low maintenance cost. Most space trusses are made of steel and aluminium whilst a few are of timber. Interest is now shifting from the traditional use of timber in plane trusses of relatively short span, to new structural forms for medium to long spans. In adopting such systems in timber for non-traditional roofing applications, the challenge lies in developing structurally sound, visually neat and economically reproducible connectors for 3-dimensional configurations of timber members. The research aimed at developing a new connector for double and triple-layer space grids in timber, intended for medium-span lightweight roofing applications. The origins of the connector date back to 1995, when it was first proposed by Zingoni as the 14FTC-U Timber Space-Truss Connector, and subsequently tested under laboratory conditions over the three years that followed. Unlike connectors for timber space grids proposed by earlier investigators, or the proprietary connector systems that are available for constructions in steel and aluminium, the 14FTC-U connector features a central core of wood in the form of a cuboctahedron or its variants, upon whose faces are attached U-shaped metal brackets that take the timber members. Thus the connector unit is predominantly wood, giving it considerable aesthetic advantages over its all-metal counterparts. While promising, the structural performance of the original connector was not adequate for practical application, hence a programme of further development was embarked upon. As reported in the thesis, the improvements of the connector have culminated in a structurally viable unit that has been successfully employed in a prototype double-layer timber grid.